Exploratory study : how do Somali shop owners (SSO) succeed in running businesses in Soweto : a South African perspective,Exploratory study : how do Somali shop owners run successful businesses in Soweto, South Africa? - Mokitlane, Ofentse Clifford (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
This is a qualitative study which seeks to understand how Somali shop owners run successful businesses in the township of Soweto in South Africa. This research report has three sections, namely (1) the academic paper which comprises a shortened literature review, the research method, findings, and the discussion; (2) an extended literature review and (3) the research methodology. It is important to mention that these three sections are related and not necessarily stand-alone sections. Despite the hostilities faced by the Somali shop owners from the host communities in South Africa, it is notable that they are successful, small-sized entrepreneurs in most townships of South Africa (SA). Previous research on Somalis has predominantly focused on their assimilation into the societies in their host countries, and on how they are led into self-employment because of the unfavourable labour markets in the host country. In this vein, there is a need to understand how they run successful businesses in the townships of SA. This study seeks to answer the following research question: How Do Somali Shop Owners Succeed in Running Businesses in Soweto, South Africa (SA)? In pursuit of answers to the above research question, this study was confined to three locations in Soweto, namely Orlando West, Chiawelo and Rockville which have a relatively high number of Somali entrepreneurs who have been in operation for longer than three years. This qualitative study explored the multiple perspectives of reality of Somali shop owners. Purposively, 14 Somali shop owners were identified initially using purposive sampling. Subsequently, theoretical sampling was used to identify Somali shop owners who were interviewed regarding how they successfully run their businesses in the locations of Orlando West, Chiawelo and Rockville in the township of Soweto. A total of eighteen semi-structured, in-depth and face-to-face interviews were conducted with these shop owners as a means of gathering data to the point of saturating their perspectives. Data collection ceased when new perspectives were no longer evident as interviewees were being repetitive. Open-coding and constant comparison was used to analyse the data. The findings of the study show that ethnicity plays a predominant role in the success of the Somali shop owners. The intra-ethnic networks and trust-based support systems are pivotal to how Somali shop owners run successful businesses in Soweto. The key findings manifested showed that various forms of support came from Somali communities, family and fellow countrymen which were also central to their success. Another key finding showed that Somali shop owners run their businesses by complementing, rather than predominantly competing with the other local businesses, which ultimately differentiates them in this way. The study also revealed that responsiveness to local customer needs by enhancing the value of their business to the locality is also characteristic of how Somali shop owners build customer loyalty. This study contributes to our understanding of how Somali entrepreneurs conduct successful businesses in a hostile host country. The findings have implications for business development training and programmes which support immigrant entrepreneurs. The findings may also be extended to inform how business development programmes would be designed to equally support local entrepreneurs.
Keywords: Business enterprises, Foreign -- South Africa; Small business -- Management; Small business -- South Africa; Foreign workers -- South Africa; Employment in foreign countries; Entrepreneurship -- South Africa